Dans l’ombre du prestige. Établissements de bains isolés et micro-stations thermales des Pyrénées occidentales - Viviane Delpech (Les Cahiers de Framespa)
In close proximity to the Western Pyrenees' prestigious spa resorts, a web of healing sources scantily exploited has welcomed local people since protohistory. From the Renaissance on, and with the development of the spa industry, these sites have equipped themselves with balneal installations in line with larger neighbouring resorts. The sample of sites under study (Camou, Fontaines d’Escot, Saint-Christau, Ogeu, Gan, Rébénacq, Bains de Secours, Beaucens) can be categorized under two distinct groups within an architectural typology: isolated bath houses, on the one hand, and micro-spa resorts, on the other, combine aspects of both vernacular architecture and trends (neoclassicism, orientalism, eclecticism) observable at the national level with more or less emphasis. This study distances itself from the association between thermalism and the elite to demonstrate instead how curative waters which, despite their apparent modesty in comparison to their more illustrious neighbours, have played a prominent and timeless role for local communities from a medical, economic, social, and even political viewpoint.